Influence of visual display near task (VDNT) on the blink rates (BR) and dry eye symptoms among soft contact lens wearer/ Aresya Najmee and Nurul Inarah Mohamad Zambri - Najmee, Aresya; Mohamad Zambri, Nurul Inarah (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
This article studies the effect of the visual display near task (VDNT) on blink rate (BR) among soft contact lens wearer and the association between blink rates with the symptoms of dry eye in habitual contact lens wearer. Eighteen participants (mean age: 22.1±1.6 years) were recruited in this study. All participants were adapted soft contact lens wearer with low to moderate power (0.00D to ≤ - 6.00D). Dry eye symptom questionnaire (CLDEQ-8) was given to each participant and asked to answer prior to the study. Blinking were then captured for 23 minutes which comprised of 3 minutes before VDNT with a 3-meter target (as baseline measurement) and another 20 minutes during VDNT at 40 centimetres. Blinking was counted by stopwatch when the ocular surface area fully covered by the upper eyelid. The Blink Rates for 1 minute was calculated from the average. The total point of CLDEQ-8 were correlated with the blink rates in both conditions. The mean of the blink rates before VDNT 23.5 blink/min (SD± 9.09 blink/min) higher than the mean of the blink rates during VDNT 11.4 blink/min (SD ± 5.03 blink/min). The mean difference of both conditions was statistically significant p < 0.05 and the 95% confidence interval (CI) was 12.15 (8.767-15.539). The weak positive correlation of dry eye symptoms and the blink rates before VDNT, r=0.104 (p=0.682) and during VDNT, r= 0.142 (p=0.573). There was no significant of dry eye symptoms and both blink rates, respectively. The blink rate/min was affected during visual display near task among soft contact lens wearer. The blink rate reduced significantly during VDNT. A good selection of subjects can influence the correlation between dry eye symptoms and blink rates. However, this study agreed that both contact lens and VDNT could be the factors that contribute to the tear film instability due to less endogenous blinking occurred when more attention required by the task.